Influence of Organizational Culture on Employee Performance with Work Stress as a Moderating Variable at the Sub-district Office of Siantar Utara Pematangsiantar City - Diana Butar-Butar; Mhd. Ramadhan; Santa Elisabet; Indah Lestari Panjaitan; Randika Saragih (Journal of Management and Business Analytics, 2025)
This study examines the influence of organizational culture on employee performance with work stress as a moderating variable at the Sub-District Office of Siantar Utara, Pematangsiantar City. The research seeks to determine the extent to which organizational culture improves employee performance and whether work stress weakens this relationship. The variables analyzed are organizational culture as the independent variable, employee performance as the dependent variable, and work stress as the moderating variable. A combination of library research and field research was applied, using both descriptive qualitative and quantitative methods. Data were collected from 40 employees through questionnaires distributed by purposive sampling. Analytical techniques used include descriptive analysis, simple linear regression, moderation regression with the absolute difference method, correlation, determination coefficient, and hypothesis testing. The results show that organizational culture positively and significantly affects employee performance, meaning that a stronger culture enhances performance. However, work stress exerts a negative and significant moderating effect, indicating that higher stress levels reduce the positive impact of organizational culture on performance. Correlation analysis reveals a very strong and positive relationship with an r-value of 0.833. The coefficient of determination shows that 69.4% of performance is explained by organizational culture, and this rises to 76.3% when stress is included as a moderator. These findings suggest that while organizational culture is critical to performance, managing stress is equally important for optimizing outcomes.